2020
DOI: 10.1186/s12879-020-05002-w
|View full text |Cite
|
Sign up to set email alerts
|

Burden of HPV related anogenital diseases in young women in Germany – an analysis of German statutory health insurance claims data from 2012 to 2017

Abstract: Background: Most individuals are infected with human papillomavirus (HPV) at least once in their lifetime. Infections with low-risk types can cause genital warts, whereas high-risk types can cause malignant tumors. The aim of this study was to determine the burden of anogenital diseases potentially related to HPV in young women based on German statutory health insurance claims data. Methods: We conducted a retrospective claims data analysis using the "Institute for Applied Health Research Berlin" (InGef) Resea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 21 publications
0
9
0
1
Order By: Relevance
“…Eine weitere Studie unter Verwendung von Versichertendaten von ca. 60.000 jungen Frauen zeigte einen signifikanten Rückgang von zervikalen Läsionen und Genitalwarzen [60]. Die Prävalenz von Genitalwarzen lag für die Geburtskohorte 1989 bei 1,30 % (95 % KI: 1,12-1,49), während in jüngeren Geburtskohorten die Prävalenz niedriger war (0,94, 95 % KI: 0,79-1,10, Geburtskohorte 1992; [60]).…”
Section: Einfluss Der Hpv-impfung Auf Krebsvorstufen Und Genitalwarzenunclassified
“…Eine weitere Studie unter Verwendung von Versichertendaten von ca. 60.000 jungen Frauen zeigte einen signifikanten Rückgang von zervikalen Läsionen und Genitalwarzen [60]. Die Prävalenz von Genitalwarzen lag für die Geburtskohorte 1989 bei 1,30 % (95 % KI: 1,12-1,49), während in jüngeren Geburtskohorten die Prävalenz niedriger war (0,94, 95 % KI: 0,79-1,10, Geburtskohorte 1992; [60]).…”
Section: Einfluss Der Hpv-impfung Auf Krebsvorstufen Und Genitalwarzenunclassified
“…In a recent study we demonstrated a substantial burden of HPV-associated anogenital diseases in 23–25-year-old women in Germany between 2012–2017 based on statutory health insurance (SHI) claims data [ 5 ]. The identified women were of special interest as these 23–25-year-olds were from the first birth cohorts eligible for HPV vaccination as adolescents after its introduction in Germany (birth cohorts 1989–1992) and because their identification enabled exploration of the burden of HPV-associated anogenital diseases in these young, less well studied age groups.…”
Section: Introductionmentioning
confidence: 99%
“…The identified women were of special interest as these 23–25-year-olds were from the first birth cohorts eligible for HPV vaccination as adolescents after its introduction in Germany (birth cohorts 1989–1992) and because their identification enabled exploration of the burden of HPV-associated anogenital diseases in these young, less well studied age groups. The most frequent diagnoses were anogenital warts with 3-year administrative prevalence rates for each birth cohort of 0.82–1.30% and grade 1 and grade 3 cervical intraepithelial neoplasia (CIN), with 3-year administrative prevalence rates of 1.31–1.60% for grade 1 lesions and 0.71–1.09% for grade 3 lesions [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 13 , 14 , 15 However, over the last two decades, its incidence has increased, particularly among young women, and this is attributed to infection with HPV. 16 , 17 , 18 , 19 …”
Section: Introductionmentioning
confidence: 99%